Determinants of dividend payout ratio: evidence from Malaysian public listed firms - Yong, Teck Mui; Mustapha, Mazlina (TextRoad Publication, 2016)
Dividend policy is a decision made by an organization to determine the amount of dividend to be paid and the level of the profit to be retained. Prior studies claimed that dividend policy can help to reduce the agency problems in the organization. Thus, this decision is very important. However, to date, there is no general consensus on the factors which influence dividend policy. Therefore, this study aims to examine the determinants of dividend policy among public-listed firms in Malaysia. Secondary data was hand-collected from the annual reports of the listed firms for a period of five years. This study employs multiple regression to estimate the relationship between the determinants and dividend payout decisions. The results indicate that investment opportunity, liquidity and firm size significantly influence the dividend payout of Malaysian listed firms. This study contributes to the literature related to dividend payout in developing countries, specifically in the Malaysian business environment. It also provides information to the managers about how their decisions would affect the agency costs of the organization.